High-strength and high-toughness TiAl intermetallic compound full-lamellar regulation and control heat treatment method

By adopting a solid solution + dual aging heat treatment process on TiAl intermetallic compounds, the microstructure is regulated, which solves the problem that traditional heat treatment methods are difficult to obtain high strength and high toughness, and achieves the high strength, high toughness and good high temperature performance of the alloy.

CN119571232APending Publication Date: 2025-03-07ANSTEEL BEIJING RES INST CO LTD +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411632848.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The traditional heat treatment method of TiAl intermetallic titanium alloy is difficult to obtain high strength, high toughness and good high temperature performance, and the microstructure caused by conventional solid solution + aging treatment processes is not conducive to the mechanical properties of the alloy.

Method used

The heat treatment process of solid solution + dual aging is adopted. The specific steps include solid solution treatment, primary aging treatment and secondary aging treatment. By controlling the temperature and time, the microstructure of TiAl intermetallic compounds is regulated.

Benefits of technology

The high strength, high toughness and good high temperature performance of TiAl intermetallic compounds are achieved, ensuring the comprehensive improvement of the room temperature and high temperature mechanical properties of the alloy, and has high industrial application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571232A_ABST
    Figure CN119571232A_ABST
Patent Text Reader

Abstract

The invention relates to a high-strength and high-toughness TiAl intermetallic compound full-lamellar regulation and control heat treatment method, which adopts a'solid solution + dual aging 'heat treatment process and comprises the following steps: 1) solid solution treatment: heating a TiAl intermetallic compound plate to 10-110 DEG C above T beta, preserving heat for more than 30 minutes at the temperature, and then water-cooling to room temperature; (2) primary aging treatment is conducted, specifically, the TiAl intermetallic compound plate is subjected to heat preservation for 6-8 h at the temperature of 800-900 DEG C; then water-cooling to room temperature; and (3) double aging treatment is conducted, specifically, the TiAl intermetallic compound plate is subjected to heat preservation for 4 h or above at the temperature of 500-600 DEG C, and then air cooling is conducted to the room temperature. According to the method, for TiAl intermetallic compound plate workpieces of any size, the room-temperature and high-temperature comprehensive mechanical properties of the TiAl intermetallic compound plate workpieces can be guaranteed, good matching of strength and plasticity can be achieved, and therefore it is guaranteed that products have better industrial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat treatment of high-temperature titanium alloys, and in particular to a method for regulating heat treatment of a full-layer sheet of a high-strength and high-toughness TiAl intermetallic compound. Background Art

[0002] With the development of aerospace technology and the improvement of weapon equipment speed and performance, higher requirements are placed on high-temperature structural materials. It has become a trend to develop materials with high strength, high toughness, high specific strength and excellent high-temperature performance and their structural parts forming technology. In order to adapt to this trend, it is urgent to develop new high-strength, high-toughness, high-temperature titanium alloys resistant to TiAl intermetallic compounds and corresponding heat treatment processes.

[0003] Heat treatment is one of the main means of adjusting the properties of high-strength and toughness titanium alloys. The heat treatment of traditional TiAl intermetallic compound titanium alloys is mainly achieved through "solution treatment + aging treatment" (such as the "Preparation method of high-niobium TiAl intermetallic compound with a heterogeneous lamellar structure with alternating coarse and fine grains" disclosed in the Chinese invention patent with authorization announcement number CN 116043053 B). By using heat treatment, the mechanical properties of titanium alloys can be significantly changed by controlling the changes in microstructure. The main strengthening phase in the titanium alloy matrix has a very important influence on its mechanical properties, its morphology, content and size. Solution treatment is mainly to obtain metastable β phase. During the aging process, the metastable β phase decomposes to form an alloy strengthened by a large number of fine dispersed aging α phases. The strength and toughness of high-strength and toughness titanium alloys strongly depend on the morphology, quantity and scale of the aging α phase, and the transformation of the aging α phase into a morphology with smaller interlamellar spacing and smaller grain size mainly depends on the aging temperature.

[0004] The general heat treatment process is to carry out solution treatment in the single-phase region above the phase transformation point or the bidirectional region below the phase transformation point. For TiAl intermetallic compounds, after conventional heat treatment, the α grain size inside the microstructure is relatively coarse and dispersed in the matrix, the spacing between the γ phase lamellae is large and the proportion is small, and the plasticity and fracture toughness of the alloy after conventional "solid solution + aging" treatment are poor.

[0005] Therefore, on the basis of the conventional "solution + aging" heat treatment process, multiple influencing factors such as temperature, time and number of aging times should be comprehensively considered to formulate a suitable heat treatment process to control the microstructural characteristics such as organizational morphology, quantity and size, which can not only further improve the strength of the TiAl intermetallic compound titanium alloy, but also ensure the plasticity and toughness of the alloy, thereby meeting the use requirements. Summary of the invention

[0006] The present invention provides a method for regulating heat treatment of a full-layer sheet of high-strength and high-toughness TiAl intermetallic compound, which adopts a "solid solution + double aging" heat treatment process. For TiAl intermetallic compound sheet workpieces of any size, the comprehensive mechanical properties at room temperature and high temperature can be guaranteed, and the strength and plasticity can be well matched, thereby ensuring that the product has better industrial application value.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A method for regulating heat treatment of a full-layer sheet of a high-strength and high-toughness TiAl intermetallic compound adopts a solid solution + double aging heat treatment process; specifically comprising the following steps:

[0009] 1) Solution treatment: Heat the TiAl intermetallic compound plate to T β Above 10-110℃, keep at this temperature for more than 30min, then cool to room temperature with water;

[0010] 2) A heavy aging treatment: the TiAl intermetallic compound plate after cooling in step 1) is kept at 800-900° C. for 6-8 hours; then water-cooled to room temperature;

[0011] 3) Double aging treatment: The TiAl intermetallic compound plate after cooling in step 2) is kept at a temperature of 500-600° C. for more than 4 hours, and then air-cooled to room temperature.

[0012] The nominal composition of the high-strength and high-toughness TiAl intermetallic compound is: Ti-44Al-4Nb-1Mo-0.5B in terms of atomic percentage.

[0013] In the step 1), the TiAl intermetallic compound plate is heated to T β The above 65-85°C, keep warm for more than 30 minutes, and then water cool to room temperature; in the step 2), the TiAl intermetallic compound plate after the cooling in step 1) is kept warm at 820-890°C for 6-8 hours; then water cool to room temperature; in the step 3), the TiAl intermetallic compound plate after the cooling in step 2) is kept warm at 520-580°C for more than 4 hours, and then air cool to room temperature; after heat treatment, the room temperature tensile strength of the TiAl intermetallic compound plate is 896-912MPa, the yield strength is 691-722MPa, and the elongation is ≥4.2%; the high temperature tensile strength at 750°C is 756-828MPa, and the high temperature yield strength at 750°C is 672-731MPa.

[0014] In the step 2), the heating furnace is preheated to 500°C and the furnace is loaded, the TiAl intermetallic compound plate is heated to 865-875°C with the furnace and kept warm for 6h-8h, the heating rate is 10°C / min, and then water-cooled to room temperature; in the step 3), the heating furnace is preheated to 400°C and the furnace is loaded, the TiAl intermetallic compound plate is heated to 545-555°C with the furnace and kept warm for more than 4h, the heating rate is 10°C / min, and then air-cooled to room temperature; after heat treatment, the room temperature tensile strength of the TiAl intermetallic compound plate is 954-1002MPa, the yield strength is 854-916MPa, and the elongation is ≥6.2%; the high temperature tensile strength at 750°C is 799-885MPa, and the high temperature yield strength at 750°C is 810-896MPa.

[0015] In the step 1), the TiAl intermetallic compound plate is heated to 1360°C and kept warm for 30 minutes. The β phase transition point Tβ of the TiAl intermetallic compound is 1290±5°C, and then cooled to room temperature with water. In the step 2), the heating furnace is preheated to 500°C and loaded into the furnace. The TiAl intermetallic compound plate is heated to 870±5°C with the furnace and kept warm for 7 hours. The heating rate is 10°C / min, and then cooled to room temperature with water. In the step 3), the heating furnace is preheated to 400°C. ℃ loading furnace, the TiAl intermetallic compound plate is heated with the furnace to 550℃±5℃ and kept warm for 4h, the heating rate is 10℃ / min, and then air-cooled to room temperature; after heat treatment, the room temperature tensile strength of the TiAl intermetallic compound plate is 946~1102MPa, the yield strength is 874~986MPa, and the elongation is ≥8.6%; the high temperature tensile strength at 750℃ is 917~945MPa, and the high temperature yield strength at 750℃ is 884~902MPa.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] 1) Compared with the conventional titanium alloy heat treatment method, the solution treatment of the present invention is β The above is carried out at a relatively high temperature, at which the original structure of the TiAl intermetallic compound can be completely converted into the α phase and the γ phase, thereby obtaining a two-phase structure with a smaller grain size and a relatively small interlamellar spacing.

[0018] 2) The present invention adopts double aging treatment, first performing an aging treatment at a slightly higher temperature, and then performing a secondary aging treatment at a lower temperature. This double aging heat treatment process can not only ensure that the α structure is completely converted into the γ lamellar structure, but also the lamellar spacing is smaller after the double aging treatment, which can enable the TiAl intermetallic compound to obtain higher comprehensive mechanical properties.

[0019] 3) In the present invention, when performing the "solution + double aging" heat treatment, the solution temperature is controlled to be T β Above 10℃~110℃, keep warm for more than 30min. Since the α phase in the original structure is densely distributed, if the temperature is too low, the γ phase lamellar structure will be less and the lamellar spacing will be larger after solution treatment; if the temperature is too high, the material will be over-burned, making the grains too coarse (up to millimeter level), which will have an adverse effect on the subsequent mechanical properties after aging treatment. After aging treatment, the matrix is ​​a two-phase structure, which cannot be completely transformed into a microstructure with a small lamellar spacing and all γ lamellar structures, which has a great influence on the yield strength and elongation of the alloy.

[0020] 4) The heat treatment process of the present invention is simple, and the room temperature and high temperature tensile strength, yield strength, elongation and other comprehensive mechanical properties of the TiAl intermetallic compound after treatment are good, which can be used as an effective means to improve the strength and plasticity of the TiAl intermetallic compound. Practice has proved that the heat treatment method of the present invention further improves the plasticity and elongation of the TiAl intermetallic compound under the premise of ensuring high strength, and the process is significantly better than the traditional heat treatment method, which has industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a microscopic morphology of the TiAl intermetallic compound after heat treatment in Example 1 of the present invention.

[0022] Figure 2 This is a microscopic morphology of the TiAl intermetallic compound after heat treatment in Example 6 of the present invention.

[0023] Figure 3 This is a microscopic morphology of the TiAl intermetallic compound after heat treatment in Example 7 of the present invention. DETAILED DESCRIPTION

[0024] The present invention discloses a method for controlling heat treatment of a full-layer sheet of a high-strength and high-toughness TiAl intermetallic compound, which adopts a "solid solution + double aging" heat treatment process. The solid solution treatment of the TiAl intermetallic compound is carried out above the phase transition point, and the double aging treatment adopts a segmented temperature control method to reach the target temperature, and then the temperature is kept and cooled at the target temperature. The specific steps are as follows:

[0025] The first step of solid solution treatment is to heat the TiAl intermetallic compound to T β Above 10℃~110℃, keep warm for more than 30min, then cool to room temperature with water;

[0026] The second step is a heavy aging treatment: the material obtained after cooling in the first step is loaded into the furnace when the furnace temperature reaches 500°C, and the temperature is raised to 800-900°C with the furnace, and kept at this temperature for 6h-8h, with a heating rate of 10°C / min, and then water-cooled to room temperature;

[0027] The third step is double aging treatment: the material obtained after cooling in the second step is loaded into the furnace when the furnace temperature reaches 400℃, and the temperature is raised to 500℃~600℃ with the furnace for more than 4h, the heating rate is 10℃ / min, and then air-cooled to room temperature.

[0028] The nominal composition of the high-strength and high-toughness TiAl intermetallic compound of the present invention is: Ti-44Al-4Nb-1Mo-0.5B (at%).

[0029] As a preferred solution, in the first step of solid solution treatment, the TiAl intermetallic compound plate is heated to T β The temperature is 65℃~85℃ and kept at this temperature for 30min, then water-cooled to room temperature; in the second step of single aging treatment, the cooled material is kept at 820℃~890℃ for 6h~8h; then water-cooled to room temperature; in the third step of double aging treatment, the cooled material is kept at 520℃~580℃ for 4h, then air-cooled to room temperature.

[0030] When this preferred scheme is adopted, the room temperature tensile strength of the obtained material reaches 896-912MPa, the yield strength reaches 691-722MPa, and the elongation reaches more than 4.2%; the high temperature tensile strength at 750°C reaches 756-828MPa, and the high temperature yield strength at 750°C reaches 672-731MPa.

[0031] As a preferred solution, in order to further improve the room temperature and high temperature comprehensive mechanical properties of the material, obtain better strength and plasticity and higher elongation, the heat treatment process of TiAl intermetallic compound is as follows:

[0032] The first step of solid solution treatment is to heat the TiAl intermetallic compound to T β Above 65℃~85℃, keep warm for more than 30min, then cool to room temperature with water;

[0033] The second step is a heavy aging treatment: the material obtained after cooling in the first step is loaded into the furnace when the furnace temperature reaches 500°C, and the temperature is raised to 865-875°C with the furnace and kept at this temperature for 6 hours at a heating rate of 10°C / min, and then water-cooled to room temperature;

[0034] The third step is double aging treatment: the material obtained after cooling in the second step is loaded into the furnace when the furnace temperature reaches 400℃, and the temperature is raised to 545-555℃ and kept at this temperature for 4h with a heating rate of 10℃ / min, and then air-cooled to room temperature.

[0035] When this preferred scheme is adopted, the room temperature tensile strength of the obtained material reaches 954-1002MPa, the yield strength reaches 854-916MPa, the elongation reaches more than 6.2%, the high temperature tensile strength at 750°C reaches 799-885MPa, and the high temperature yield strength at 750°C reaches 810-896MPa.

[0036] When this preferred solution is adopted, the microstructure after the first step of solid solution treatment is a large-grained α phase and a large-scale γ phase with a large lamellar spacing, wherein the lamellar occupies a relatively small proportion and is large in size, with an average grain size of 63μm and a volume fraction of 36%. After the second step of single-stage aging treatment and cooling to room temperature, the proportion of the α phase decreases, the proportion of the lamellar crystal clusters of the γ phase increases, and the spacing between the crystal clusters decreases, with an average grain size of 41μm and a volume fraction of 55%; after the third step of double-stage aging treatment and cooling to room temperature, the microstructure of the material is mostly a full-lamellar γ phase, with a reduced spacing between the crystal clusters, and an average grain size of 32μm and a volume fraction of 92%.

[0037] In the present invention, under the premise of ensuring the tensile strength, in order to further improve the yield strength and at the same time improve the elongation, the following preferred solutions can be selected:

[0038] The first step is solution treatment: the TiAl intermetallic compound plate is heated to 1360°C and kept at this temperature for 30 minutes, wherein the β phase transition point of the TiAl intermetallic compound is 1290±5°C, and then cooled to room temperature with water;

[0039] The second step is a heavy aging treatment: the material obtained after cooling in the first step is loaded into the furnace when the furnace temperature reaches 500℃, and the temperature is raised to 870±5℃ and kept at this temperature for 7h, with a heating rate of 10℃ / min, and then water-cooled to room temperature;

[0040] The third step is double aging treatment: the material obtained after cooling in the second step is loaded into the furnace when the furnace temperature reaches 400℃, and the temperature is raised to 550℃±5℃ with the furnace, and kept at this temperature for 4h, with a heating rate of 10℃ / min, and then air-cooled to room temperature;

[0041] When this preferred scheme is adopted, the room temperature tensile strength of the obtained material reaches 946-1102MPa, the yield strength reaches 874-986MPa, and the elongation reaches more than 8.6%; the high temperature tensile strength at 750°C reaches 917-945MPa, and the high temperature yield strength at 750°C reaches 884-902MPa.

[0042] When this preferred solution is adopted, the microstructure after the first step of solid solution treatment is lamellar crystal clusters with different lamellar spacing and grain sizes and α phases with different grain sizes, among which the lamellar occupies a relatively small proportion and is larger in size, with an average grain size of 40μm and a volume fraction of 41%. After the second step of single aging treatment and cooling to room temperature, the proportion of lamellar crystal clusters of the γ phase increases, the spacing between the crystal clusters decreases, and the average grain size is 15μm, with a volume fraction of 62%; after the third step of double aging treatment and cooling to room temperature, the proportion of lamellar crystal clusters of the γ phase increases to become a full lamellar structure, the spacing between the crystal clusters decreases, and the average grain size is 5μm, with a volume fraction of 100%.

[0043] The following embodiments are implemented on the premise of the technical solution of the present invention, and provide detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following embodiments.

[0044] [Example 1]

[0045] This embodiment provides a method for regulating heat treatment of a full-layer TiAl intermetallic compound sheet with high strength and high toughness. A TiAl intermetallic compound sheet (hereinafter referred to as material) with a size of 5 mm×110 mm×180 mm is heat treated. The specific steps are as follows:

[0046] The first step of solution treatment: heat the material to T β Above 110℃, keep warm for 30min and then cool to room temperature with water;

[0047] The second step is a heavy aging treatment: the material obtained after cooling in the first step is loaded into the furnace when the furnace temperature reaches 500°C, and the temperature is raised to 900°C with the furnace for 8 hours, the heating rate is 10°C / min, and then water-cooled to room temperature;

[0048] The third step is double aging treatment: the material obtained after cooling in the second step is loaded into the furnace when the furnace temperature reaches 400℃, and the temperature is raised to 600℃ and kept for 4h with the heating rate of 10℃ / min, and then air-cooled to room temperature.

[0049] After pre-grinding, polishing and etching, the heat-treated TiAl intermetallic compound sample of this embodiment was observed for microscopic morphology using an electron microscope, and its mechanical properties were tested using a universal testing machine. The room temperature mechanical property parameters of the heat-treated TiAl intermetallic compound of this embodiment are shown in Table 1.

[0050] The average tensile strength of the TiAl intermetallic compound after heat treatment in this embodiment is 759 MPa (maximum value is 821 MPa), the average yield strength is 591 MPa (maximum value is 676 MPa), the average elongation is 3.17% (maximum value is 3.32%), the average high-temperature tensile strength at 750°C is 652 MPa (maximum value is 678 MPa), and the average high-temperature yield strength at 750°C is 581 MPa (maximum value is 593 MPa).

[0051] Figure 1 The microscopic morphology of the TiAl intermetallic compound after heat treatment in this embodiment is shown in FIG. Figure 1 It can be seen that the α phase is evenly distributed with a size of 21 to 30 μm, while the interlamellar spacing of the γ structure is larger, accounting for a smaller proportion (only 35%), and the size is 35 to 45 μm.

[0052] [Example 2]

[0053] This embodiment provides a method for controlling heat treatment of a full-layer sheet of a high-strength and high-toughness TiAl intermetallic compound. A TiAl intermetallic compound sheet with a size of 5 mm×110 mm×180 mm is heat treated. The specific steps are as follows:

[0054] The first step of solution treatment: heat the material to T β Above 20℃, keep warm for 30min and then cool to room temperature with water;

[0055] The second step is a heavy aging treatment: the material obtained after cooling in the first step is loaded into the furnace when the furnace temperature reaches 500°C, and the temperature is raised to 850°C with the furnace and kept for 8 hours at a heating rate of 10°C / min, and then water-cooled to room temperature;

[0056] The third step is double aging treatment: the material obtained after cooling in the second step is loaded into the furnace when the furnace temperature reaches 400℃, and the temperature is raised to 600℃ and kept for 4h with the heating rate of 10℃ / min, and then air-cooled to room temperature.

[0057] After pre-grinding, polishing and etching, the TiAl intermetallic compound sample heat-treated in this embodiment was observed for microscopic morphology using an electron microscope, and its mechanical properties were tested using a universal testing machine. The room temperature mechanical property parameters of the TiAl intermetallic compound heat-treated in this embodiment are shown in Table 1.

[0058] The average tensile strength of the TiAl intermetallic compound after heat treatment in this embodiment is 744MPa (maximum value is 789MPa), the average yield strength is 585MPa (maximum value is 623MPa), the average elongation is 3.04% (maximum value is 3.11%), the average high-temperature tensile strength at 750°C is 632MPa (maximum value is 648MPa), and the average high-temperature yield strength at 750°C is 572MPa (maximum value is 583MPa).

[0059] [Example 3]

[0060] This embodiment provides a method for controlling heat treatment of a full-layer sheet of a high-strength and high-toughness TiAl intermetallic compound. A TiAl intermetallic compound sheet with a size of 5 mm×110 mm×180 mm is heat treated. The specific steps are as follows:

[0061] The first step of solution treatment: heat the material to T β Above 65℃, keep warm for 30min and then cool to room temperature with water;

[0062] The second step is a heavy aging treatment: the material obtained after cooling in the first step is loaded into the furnace when the furnace temperature reaches 500°C, and the temperature is raised to 830°C with the furnace for 8 hours, the heating rate is 10°C / min, and then water-cooled to room temperature;

[0063] The third step is double aging treatment: the material obtained after cooling in the second step is loaded into the furnace when the furnace temperature reaches 400℃, and the temperature is raised to 580℃ and kept for 4h with the heating rate of 10℃ / min, and then air-cooled to room temperature.

[0064] After pre-grinding, polishing and etching, the TiAl intermetallic compound sample heat-treated in this embodiment was observed for microscopic morphology using an electron microscope, and its mechanical properties were tested using a universal testing machine. The room temperature mechanical property parameters of the TiAl intermetallic compound heat-treated in this embodiment are shown in Table 1.

[0065] The average tensile strength of the TiAl intermetallic compound after heat treatment in this embodiment is 901MPa (maximum value is 909MPa), the average yield strength is 702MPa (maximum value is 719MPa), the average elongation is 3.94% (maximum value is 4.02%), the average high-temperature tensile strength at 750°C is 776MPa (maximum value is 795MPa), and the average high-temperature yield strength at 750°C is 684MPa (maximum value is 701MPa).

[0066] [Example 4]

[0067] This embodiment provides a method for controlling heat treatment of a full-layer sheet of a high-strength and high-toughness TiAl intermetallic compound. A TiAl intermetallic compound sheet with a size of 5 mm×110 mm×180 mm is heat treated. The specific steps are as follows:

[0068] The first step of solution treatment: heat the material to T β Above 85℃, keep warm for 30min and then cool to room temperature with water;

[0069] The second step is a heavy aging treatment: the material obtained after cooling in the first step is loaded into the furnace when the furnace temperature reaches 500°C, and the temperature is raised to 880°C with the furnace for 8 hours, the heating rate is 10°C / min, and then water-cooled to room temperature;

[0070] The third step is double aging treatment: the material obtained after cooling in the second step is loaded into the furnace when the furnace temperature reaches 400℃, and the temperature is raised to 540℃ and kept for 4h with the heating rate of 10℃ / min, and then air-cooled to room temperature.

[0071] After pre-grinding, polishing and etching, the TiAl intermetallic compound sample heat-treated in this embodiment was observed for microscopic morphology using an electron microscope, and its mechanical properties were tested using a universal testing machine. The room temperature mechanical property parameters of the TiAl intermetallic compound heat-treated in this embodiment are shown in Table 1.

[0072] The average tensile strength of the TiAl intermetallic compound after heat treatment in this embodiment is 911 MPa (maximum value is 912 MPa), the average yield strength is 716 MPa (maximum value is 722 MPa), the average elongation is 4.21% (maximum value is 4.26%), the average high-temperature tensile strength at 750°C is 816 MPa (maximum value is 828 MPa), and the average high-temperature yield strength at 750°C is 726 MPa (maximum value is 731 MPa).

[0073] [Example 5]

[0074] This embodiment provides a method for controlling heat treatment of a full-layer sheet of a high-strength and high-toughness TiAl intermetallic compound. A TiAl intermetallic compound sheet with a size of 5 mm×110 mm×180 mm is heat treated. The specific steps are as follows:

[0075] The first step of solution treatment: heat the material to T β Above 65℃, keep warm for 30min and then cool to room temperature with water;

[0076] The second step is a heavy aging treatment: the material obtained after cooling in the first step is loaded into the furnace when the furnace temperature reaches 500°C, and the temperature is raised to 865°C with the furnace for 6 hours, the heating rate is 10°C / min, and then water-cooled to room temperature;

[0077] The third step is double aging treatment: the material obtained after cooling in the second step is loaded into the furnace when the furnace temperature reaches 400℃, and the temperature is raised to 545℃ and kept for 4h with the heating rate of 10℃ / min, and then air-cooled to room temperature.

[0078] After pre-grinding, polishing and etching, the TiAl intermetallic compound sample heat-treated in this embodiment was observed for microscopic morphology using an electron microscope, and its mechanical properties were tested using a universal testing machine. The room temperature mechanical property parameters of the TiAl intermetallic compound heat-treated in this embodiment are shown in Table 1.

[0079] The average tensile strength of the TiAl intermetallic compound after heat treatment in this embodiment is 987MPa (maximum value reaches 995MPa), the average yield strength is 868MPa (maximum value reaches 881MPa), the average elongation is 5.91% (maximum value reaches 6.02%), the average high-temperature tensile strength at 750°C is 826MPa (maximum value reaches 838MPa), and the average high-temperature yield strength at 750°C is 832MPa (maximum value reaches 845MPa).

[0080] [Example 6]

[0081] This embodiment provides a method for controlling heat treatment of a full-layer sheet of a high-strength and high-toughness TiAl intermetallic compound. A TiAl intermetallic compound sheet with a size of 5 mm×110 mm×180 mm is heat treated. The specific steps are as follows:

[0082] The first step of solution treatment: heat the material to T β Above 85℃, keep warm for 30min and then cool to room temperature with water;

[0083] The second step is a heavy aging treatment: the material obtained after cooling in the first step is loaded into the furnace when the furnace temperature reaches 500°C, and the temperature is raised to 875°C with the furnace for 6 hours, the heating rate is 10°C / min, and then water-cooled to room temperature;

[0084] The third step is double aging treatment: the material obtained after cooling in the second step is loaded into the furnace when the furnace temperature reaches 400℃, and the temperature is raised to 555℃ and kept for 4h with the heating rate of 10℃ / min, and then air-cooled to room temperature.

[0085] After pre-grinding, polishing and etching, the TiAl intermetallic compound sample heat-treated in this embodiment was observed for microscopic morphology using an electron microscope, and its mechanical properties were tested using a universal testing machine. The room temperature mechanical property parameters of the TiAl intermetallic compound heat-treated in this embodiment are shown in Table 1.

[0086] The average tensile strength of the TiAl intermetallic compound after heat treatment in this embodiment is 998MPa (maximum value reaches 1002MPa), the average yield strength is 912MPa (maximum value reaches 916MPa), the average elongation is 6.20% (maximum value reaches 6.29%), the average high-temperature tensile strength at 750°C is 879MPa (maximum value reaches 885MPa), and the average high-temperature yield strength at 750°C is 885MPa (maximum value reaches 896MPa).

[0087] Figure 2 The microscopic morphology of the TiAl intermetallic compound after the thermal process in this embodiment is shown in FIG. Figure 2It can be seen that the α phase is evenly distributed with a size of 5 to 10 μm, the interlamellar spacing of the γ structure decreases, the proportion increases (to 70%), and the size is 10 to 15 μm.

[0088] [Example 7]

[0089] This embodiment provides a method for controlling heat treatment of a full-layer sheet of a high-strength and high-toughness TiAl intermetallic compound. A TiAl intermetallic compound sheet with a size of 5 mm×110 mm×180 mm is heat treated. The specific steps are as follows:

[0090] The first step of solution treatment: the material is heated to 1360℃ (TiAl intermetallic compound β phase transformation point T β 1290±5℃), keep warm for 30min and then cool to room temperature with water;

[0091] The second step is a heavy aging treatment: the material obtained after cooling in the first step is loaded into the furnace when the furnace temperature reaches 500°C, and the temperature is raised to 870°C with the furnace for 7 hours, the heating rate is 10°C / min, and then water-cooled to room temperature;

[0092] The third step is double aging treatment: the material obtained after cooling in the second step is loaded into the furnace when the furnace temperature reaches 400℃, and the temperature is raised to 550℃ and kept for 4h with the heating rate of 10℃ / min, and then air-cooled to room temperature.

[0093] After pre-grinding, polishing and etching, the TiAl intermetallic compound sample heat-treated in this embodiment was observed for microscopic morphology using an electron microscope, and its mechanical properties were tested using a universal testing machine. The room temperature mechanical property parameters of the TiAl intermetallic compound heat-treated in this embodiment are shown in Table 1.

[0094] The average tensile strength of the TiAl intermetallic compound after heat treatment in this embodiment is 1098MPa (maximum value is 1102MPa), the average yield strength is 974MPa (maximum value is 986MPa), the average elongation is 8.68% (maximum value is 9.11%), the average high-temperature tensile strength at 750°C is 921MPa (maximum value is 945MPa), and the average high-temperature yield strength at 750°C is 891MPa (maximum value is 902MPa).

[0095] Figure 3 The microscopic morphology of the TiAl intermetallic compound after heat treatment in this embodiment is shown in FIG. Figure 3 It can be seen that the matrix structure is all γ structure, the interlamellar spacing is very small, accounting for 100%, and the size is 2 to 5 μm.

[0096] [Comparative Example 1]

[0097] In this example, a TiAl intermetallic compound plate with a size of 5 mm × 110 mm × 180 mm is heat treated. The specific steps are as follows:

[0098] The first step of solution treatment: heat the material to 1280℃, keep it warm for 30min and then cool it to room temperature with water;

[0099] The second step is aging treatment: the material obtained after cooling in the first step is loaded into the furnace when the furnace temperature reaches 500℃, and the temperature is raised to 800℃ and kept at this temperature for 8h at a heating rate of 10℃ / min, and then water-cooled to room temperature.

[0100] After pre-polishing and etching, the heat-treated TiAl intermetallic compound samples were observed using an electron microscope for microscopic morphology and tested for mechanical properties using a universal testing machine. The room temperature mechanical properties of the treated TiAl intermetallic compound are shown in Table 1.

[0101] The average tensile strength of the TiAl intermetallic compound after heat treatment in this example is 701 MPa, the average yield strength is 542 MPa, the average elongation is 2.84%, the average high-temperature tensile strength at 750°C is 599 MPa, and the average high-temperature yield strength at 750°C is 456 MPa.

[0102] [Comparative Example 2]

[0103] In this example, a TiAl intermetallic compound plate with a size of 5 mm × 110 mm × 180 mm is heat treated. The specific steps are as follows:

[0104] The first step of solution treatment: heat the material to 1320℃, keep it warm for 30min and then cool it to room temperature with water;

[0105] The second step is aging treatment: the material obtained after cooling in the first step is loaded into the furnace when the furnace temperature reaches 500℃, and the temperature is raised to 830℃ and kept for 8h with the heating rate of 10℃ / min, and then water-cooled to room temperature.

[0106] After pre-polishing and etching, the heat-treated TiAl intermetallic compound samples were observed using an electron microscope for microscopic morphology and tested for mechanical properties using a universal testing machine. The room temperature mechanical properties of the treated TiAl intermetallic compound are shown in Table 1.

[0107] The average tensile strength of the TiAl intermetallic compound after heat treatment in this example is 687 MPa, the average yield strength is 569 MPa, the average elongation is 2.94%, the average high-temperature tensile strength at 750°C is 584 MPa, and the average high-temperature yield strength at 750°C is 492 MPa.

[0108] [Comparative Example 3]

[0109] In this example, a TiAl intermetallic compound plate with a size of 5 mm × 110 mm × 180 mm is heat treated. The specific steps are as follows:

[0110] The first step of solution treatment: heat the material to 1320℃, keep it warm for 30min and then cool it to room temperature with water;

[0111] The second step is aging treatment: the material obtained after cooling in the first step is loaded into the furnace when the furnace temperature reaches 500℃, and the temperature is raised to 830℃ and kept for 6h with the heating rate of 10℃ / min, and then water-cooled to room temperature.

[0112] After pre-polishing and etching, the heat-treated TiAl intermetallic compound samples were observed using an electron microscope for microscopic morphology and tested for mechanical properties using a universal testing machine. The room temperature mechanical properties of the treated TiAl intermetallic compound are shown in Table 1.

[0113] The average tensile strength of the TiAl intermetallic compound after heat treatment in this example is 691 MPa, the average yield strength is 571 MPa, the average elongation is 3.01%, the average high-temperature tensile strength at 750°C is 571 MPa, and the average high-temperature yield strength at 750°C is 503 MPa.

[0114] Table 1 Mechanical properties of TiAl intermetallic compounds obtained in Examples and Comparative Examples

[0115]

[0116] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for regulating heat treatment of a full-layer sheet of high-strength and high-toughness TiAl intermetallic compound, characterized in that: The solid solution + double aging heat treatment process is adopted; the specific steps include: 1) Solution treatment: Heat the TiAl intermetallic compound plate to T β Above 10-110℃, keep at this temperature for more than 30min, then cool to room temperature with water; 2) A heavy aging treatment: the TiAl intermetallic compound plate after cooling in step 1) is kept at 800-900° C. for 6-8 hours; then water-cooled to room temperature; 3) Double aging treatment: The TiAl intermetallic compound plate after cooling in step 2) is kept at a temperature of 500-600° C. for more than 4 hours, and then air-cooled to room temperature.

2. A method for controlling heat treatment of a full-layer high-strength and high-toughness TiAl intermetallic compound according to claim 1, characterized in that: The nominal composition of the high-strength and high-toughness TiAl intermetallic compound is: Ti-44Al-4Nb-1Mo-0.5B in terms of atomic percentage.

3. The method for controlling heat treatment of a full-layer high-strength and high-toughness TiAl intermetallic compound according to claim 1, characterized in that: In the step 1), the TiAl intermetallic compound plate is heated to T β The above 65-85°C, keep warm for more than 30 minutes, and then water cool to room temperature; in the step 2), the TiAl intermetallic compound plate after the cooling in step 1) is kept warm at 820-890°C for 6-8 hours; then water cool to room temperature; in the step 3), the TiAl intermetallic compound plate after the cooling in step 2) is kept warm at 520-580°C for more than 4 hours, and then air cool to room temperature; after heat treatment, the room temperature tensile strength of the TiAl intermetallic compound plate is 896-912MPa, the yield strength is 691-722MPa, and the elongation is ≥4.2%; the high temperature tensile strength at 750°C is 756-828MPa, and the high temperature yield strength at 750°C is 672-731MPa.

4. The method for controlling heat treatment of a full-layer high-strength and high-toughness TiAl intermetallic compound according to claim 1, characterized in that: In the step 2), the heating furnace is preheated to 500°C and the furnace is loaded, the TiAl intermetallic compound plate is heated to 865-875°C with the furnace and kept warm for 6h-8h, the heating rate is 10°C / min, and then water-cooled to room temperature; in the step 3), the heating furnace is preheated to 400°C and the furnace is loaded, the TiAl intermetallic compound plate is heated to 545-555°C with the furnace and kept warm for more than 4h, the heating rate is 10°C / min, and then air-cooled to room temperature; after heat treatment, the room temperature tensile strength of the TiAl intermetallic compound plate is 954-1002MPa, the yield strength is 854-916MPa, and the elongation is ≥6.2%; the high temperature tensile strength at 750°C is 799-885MPa, and the high temperature yield strength at 750°C is 810-896MPa.

5. The method for controlling heat treatment of a full-layer high-strength and high-toughness TiAl intermetallic compound according to claim 1, characterized in that: In the step 1), the TiAl intermetallic compound plate is heated to 1360°C and kept warm for 30 minutes, the TiAl intermetallic compound β phase transition point Tβ is 1290±5°C, and then water-cooled to room temperature; in the step 2), the heating furnace is preheated to 500°C and loaded into the furnace, the TiAl intermetallic compound plate is heated to 870±5°C with the furnace and kept warm for 7 hours, the heating rate is 10°C / min, and then water-cooled to room temperature; in the step 3), the heating furnace is preheated to 400°C and loaded into the furnace, the TiAl intermetallic compound plate is heated to 550°C±5°C with the furnace and kept warm for 4 hours, the heating rate is 10°C / min, and then air-cooled to room temperature; After heat treatment, the room temperature tensile strength of the TiAl intermetallic compound plate is 946-1102MPa, the yield strength is 874-986MPa, and the elongation is ≥8.6%; the high temperature tensile strength at 750°C is 917-945MPa, and the high temperature yield strength at 750°C is 884-902MPa.

Citation Information

Patent Citations

  • A high-niobium TiAl intermetallic compound with alternating coarse and fine grains and its preparation method.

    CN116043053B